Malaysian women's autobiographies as a multiethnic legacy of generativity - Omar, Haslina (2013)
In light of autobiography scholars like Sidonie Smith and Julia Watson working towards redressing inattentiveness towards women‟s life writing, and as scholars on women‟s autobiography beyond the Western world begin to closely examine collections of works from their own countries, this study merges contemporary studies on women‟s autobiographical writings and the literary studies of Shirley Lim, as well as Nor Faridah Abdul Manaf and Muhammad A. Quayum in the area of Malaysian women‟s writings. The special focus on the representation of ethnicity in autobiography explains this study‟s exploration of a collection of autobiographies of Malaysian women belonging to four different ethnicities—Malay, Chinese, Indian and Eurasian. This study attempts to carefully explore the life stories of Sybil Kathigasu in No Dram of Mercy (1954), Khatijah Sidek in Memoirs of Khatijah Sidek (2001), Angela Yong in One Thing Good but Not Both (1998), and Muthammal Palanisamy in From Shore to Shore (2002). Women‟s autobiographies such as these evidence the assertion that their lives are of interest and value to the wider society (Borelli, “Telling It Slant” 356). The preponderance of men‟s autobiographies in major Malaysian bookstores, however, seems to perpetuate a kind of indifference towards women‟s autobiographies. Still, it is the stories of our mothers that we first listen to as children, as mothers around the world assume the biological role of nurturers and caregivers—teaching values and moral codes, as well as telling stories of their ancestors and cultural origins. These women perform an act that is “fundamental to what it is to be human” (Bosak,“What is Legacy?” n.p.),namely, passing on their legacy to their children. Any study that aims to bring attention to Malaysian women‟s autobiographies requires a reformulation of thinking and interpretation; as such, this study takes the perspective of a psycho-literary approach to the interpretation of autobiographies by multiethnic Malaysian women. This approach centres on an instinctual drive that Erik Erikson terms generativity,which is an important virtue of adulthood (McAdams The Redemptive Self, 5), and which inclines highly generative adults towards narrating their life stories sequenced in redemptive themes, and towards the desire to leave something positive behind to the community and future generations. This study carefully explores the interaction of multiethnic women‟s lives and their writings, their use of literature as a tool to extend their legacy even further, and generate outcomes that can instil wisdom,understanding and a sense of national belonging in a multiethnic community through the fostering of solidarity spurred by the willingness to blur the barriers that may exist between gender, race, class, culture and ethnicity.